Chronic Obstructive Pulmonary Disease Patients With Community‐Acquired Pneumonia on Inhaled Corticosteroid Therapy: A Comprehensive Analysis of Risk Factors, Disease Burden, and Prevention Strategies - Muhammad Muneeb Hassan; Sheikh Muhammad Sikandar; Farrukh Jamal; Muhammad Ameeq; Alpha Kargbo (Health Science Reports)
ABSTRACT Background Chronic obstructive pulmonary disease (COPD) patients commonly exhibit significant morbidity and experience a diminished quality of life. Since there has been no prior research on pneumonia in our study population, we carried out this study to learn more about the situation. Methods A retrospective analysis of 912 COPD patients with CAP who were receiving ICS treatment at the DHQ Hospital in Muzaffargarh, Punjab, Pakistan was conducted. Study began in February 2022 and ended in February 2023. Using multinomial logistic regression, the odds ratio and relative risk and Kaplan–Meier curves showed time‐to‐death and recovery by COPD status. Results Patients with COPD having a smoking history from 25 pack years and above had 22.791 higher odds of CAP (95% CI: 20.413–31.515), 21.527 higher odds of HTN (95% CI: 12.323–57.103), 16.955 higher odds of diabetes (95% CI: 22.954–29.331), and 13.964 higher odds of death in severity without COVID‐19 vaccination (95% CI: 5.988–32.561) compared to patients with COPD having a smoking history from 10 to 15 pack years. Conclusion COPD patients with a shorter ICS duration had a lower CAP risk, and vice versa, while vaccinated patients had a less severe disease as compared to non‐vaccinated patients.